2019
DOI: 10.3389/fmicb.2019.02709
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Proteomic Approach to Study the Non-lethal Effects of Silver Nanoparticles on a Gut Bacterium

Abstract: Among all the food-related nanoparticles consumed every day, silver nanoparticles (AgNPs) have become one of the most commonly utilized because of their antimicrobial properties. Despite their common use, the effects of sublethal concentrations of AgNPs, especially on gut biofilms, have been poorly investigated. To address this issue, we investigated in vitro the proteomic response of a monospecies Escherichia coli gut biofilm to chronic and acute exposures in sublethal concentrations of AgNPs. We used a new g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The most often studied ENM type at sub-inhibitory effect levels was Ag, similarly to the studies using inhibitory ENM levels. A novel gel- and label-free proteomic approach was used to explore the effects of sublethal concentrations of Ag NPs on E. coli biofilms as a model for gut bacteria ( Domingo et al, 2019 ). The new method yielded 212 differentially expressed proteins which is approximately a 6 times higher value than the average number of differentially expressed proteins in all the other proteomics studies using sub-inhibitory concentrations of ENMs, suggesting that advanced technologies may benefit omics approaches with increased detection sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The most often studied ENM type at sub-inhibitory effect levels was Ag, similarly to the studies using inhibitory ENM levels. A novel gel- and label-free proteomic approach was used to explore the effects of sublethal concentrations of Ag NPs on E. coli biofilms as a model for gut bacteria ( Domingo et al, 2019 ). The new method yielded 212 differentially expressed proteins which is approximately a 6 times higher value than the average number of differentially expressed proteins in all the other proteomics studies using sub-inhibitory concentrations of ENMs, suggesting that advanced technologies may benefit omics approaches with increased detection sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with Gram-positive bacteria have shown that Ag NPs at sub-growth-inhibitory concentrations affect the production of quorum-sensing-related proteins [57]. Sub-lethal levels of Ag NPs have also been shown to affect proteins associated with biofilm formation of Gram-negative bacteria [58], suggesting interference with bacterial signaling and functional compound secretion. While low concentrations of certain types of metal NPs that contain biologically active metals (such as ZnO) can stimulate quorum sensing and biofilm formation via providing additional nutrients [59], Ag NPs as a non-essential metal NP may have a different effect.…”
Section: Ag and Ha-au Np Effects On The Bacteriocin Gene Expression O...mentioning
confidence: 99%
“…The results demonstrated that this method could be utilized to monitor bacterial proliferation in real time without interfering with the living organisms. Mass spectrometry was successfully used for AST in a urinary tract infection [ 146 ] and to study the non-lethal effects of Ag nanoparticles on a gut bacterium [ 147 ] by monitoring bacterial growth. It is reasonable to believe that this method will be useful for determining the antimicrobial activity of ENMs including via portable mass spectrometry [ 148 ].…”
Section: Emerging Alternativesmentioning
confidence: 99%